2022
DOI: 10.1038/s41598-022-14264-0
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and oviposition patterns of Lycorma delicatula (Hemiptera: Fulgoridae) during the oviposition period in Ailanthus altissima (Simaroubaceae)

Abstract: The spotted lanternfly (SLF), Lycorma delicatula (Hemiptera: Fulgoridae), has the potential to become a global pest and is currently expanding its range in the United States. In this study, we investigated the dispersal patterns of SLF in Ailanthus altissima during its oviposition period in South Korea using a fluorescent marking system. Oviposition patterns of SLF were then analyzed by surveying egg masses in A. altissima patches. The recapture rate of fluorescent-marked SLF rapidly decreased to 30% within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Permanent markings including clipping, puncturing, and mutilation have been used mainly for coleopteran insects due to their hard elytra ( Unruh and Chauvin 1993 , Butler et al 2012 ). Color marking, especially fluorescent marking paired with ultraviolet light source, has been proven effective for investigating abundance and dispersal pattern of multiple insect species including mosquitoes, stinkbugs, and lanternflies ( Verhulst et al 2013 , Dickens and Brant 2014 , Rice et al 2015 , Kho et al 2019 , Keller et al 2020 , Jung et al 2022 ). Radio tracking allows real-time tracking of insect location even without clear sight of the insect unlike color marking.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent markings including clipping, puncturing, and mutilation have been used mainly for coleopteran insects due to their hard elytra ( Unruh and Chauvin 1993 , Butler et al 2012 ). Color marking, especially fluorescent marking paired with ultraviolet light source, has been proven effective for investigating abundance and dispersal pattern of multiple insect species including mosquitoes, stinkbugs, and lanternflies ( Verhulst et al 2013 , Dickens and Brant 2014 , Rice et al 2015 , Kho et al 2019 , Keller et al 2020 , Jung et al 2022 ). Radio tracking allows real-time tracking of insect location even without clear sight of the insect unlike color marking.…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature is incomplete about SLF's maximum dispersal potential, prior research has demonstrated dispersal estimates of less than 30 m per day (Myrick and Baker 2019, Wolfin et al 2019, Keller et al 2020a). Wolfin et al (2020), however, posited that despite average flight-bouts being less than 30 m, some SLF may hypothetically travel farther than 3,000 m following multiple flight-bouts given ideal conditions and lack of landing cues (with actual kilometer-scale dispersal confirmed by Jung et al 2022). SLF dispersal capability has also been shown to vary by life stage with greater flight distances traveled by early-season adults (Nixon et al 2021) and reduced flight capability in mated females (Wolfin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Location of egg masses can vary within a tree and are correlated to tree height. For example it was found that egg masses on TOH were concentrated towards the lower 2.5 m of the tree in areas where trees were < 6 m in height ( 14 ). Another study ( 15 ) found egg masses concentrated above 6 m on TOH when tree height ranged from 5.5 - 23.8 m. SLF egg mass survey activities are common during winter months and have been used to assess populations and gauge infestation levels ( 15 ), however the cryptic nature of SLF egg masses and the fact that eggs are most likely higher up in the canopy make visual egg mass surveys unreliable.…”
Section: Introductionmentioning
confidence: 99%